FEATURES OF THE CLINICAL PICTURE OF TESTICULAR TORSION AND ITS APPENDAGE IN CHILDREN - Firdavs Mukhitdinovich Tukhtaev; Farkhod Shavkatovich Mavlyanov; Shavkat Khojamkulovich Mavlyanov (Research Focus International Scientific Journal, 2024)
The study is aimed at developing diagnostic criteria and tactics for the treatment of emergency conditions of the genitourinary system in children, based on the methods of comprehensive urological examination. The aim of the study is to identify the features of the clinical picture in children with testicular torsion and its appendage. The results of the study are based on a prospective controlled analysis of data from 142 patients with emergency pathology of the genital organs. As part of the diagnosis of acute genital diseases in children, special attention was paid to the characteristics of the local status. The diagnostic value of the local status was studied separately for patients with Morgagni hydatid torsion and testicular torsion. The analysis of the clinical picture carried out during the study revealed new opportunities for expanding the list of anamnestic and clinical symptoms that can be included in the existing list of supporting signs for the diagnosis of these conditions.